A Systematic Review of the Quality of IV Fluid Therapy in Veterinary Medicine - Muir, William W.; Ueyama, Yukie; Noel-Morgan, Jessica; Kilborne, Allison; Page, Jessica (Frontiers in Veterinary Science, 2017)
Objective To evaluate the quality of the veterinary literature investigating IV fluid therapy in dogs, cats, horses and cattle. Design Systematic review Procedures The preferred reporting of items for systematic review and Meta-Analysis protocols (PRISMA-P) was employed for systematic review of all relevant IV fluid therapy manuscripts published from January1969 through December 2016 in the commonwealth agricultural bureau international (CABI) database. Independent grading systems used to evaluate manuscripts included the updated CONsolidated Standards of Reporting Trials (CONSORT) 2012 checklist, risk of bias (RoB) for animal intervention studies, criteria for levels of evidence, and methodological quality (Jadad scale). The quality of articles published before and after 2010 was compared. Results One hundred and thirty nine articles (63 dog, 7 cat, 39 horse, 30 cattle) from 7258 met the inclusion criteria. More than 50% of the manuscripts did not comply with minimal requirements for reporting randomized controlled trials. The most noncompliant items included identification of specific predefined objectives or a hypothesis, identification of trial design, how sample size was determined, randomization and blinding procedures. Most studies were underpowered and at risk for selection, performance, and detection bias. The overall quality of the articles improved for articles published after 2010. Conclusion and Clinical Relevance Most of the veterinary literature investigating the administration of IV fluid therapy in dogs, cats, horses and cattle is descriptive, does not comply with standards for evidence or provide adequate translation to clinical practice. Authors should employ and journal editors should enforce international consensus recommendations and guidelines for publication of data from animal experiments investigating IV fluid therapy.